Local governance's capacity to direct its own path of sustainable development - Platje, Joost (Research Papers of Wrocław University of Economics, 2011)
In this paper, some factors influencing local governance's capacity to direct its own development are discussed. This capacity is weakened by globalization processes and weakening of the nation state. It creates opportunities for powerful global stakeholders to force their economic interests, which poses a threat to sustainable development. It is argued that large urban areas, integrated in the global economy, with a high level of institutional capital as well as economic and political power, are most likely to be able to influence their own development path. However, strong self-organization may empower less developed areas. In this context, the importance of multilevel governance is discussed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 241, s. 310-318
Keywords: local governance; sustainable development; capacity building; institutional capital; institutional governance; lokalne współrządzenie; rozwój zrównoważony; kapitał instytucjonalny